Trends in birth attendants in Sudan using three consecutive household surveys (from 2006 to 2014) - Altijani, Noon; Khogali, Mustafa; Hinton, Lisa; Opondo, Charles; Eljack, Eman; Knight, Marian; Nair, Manisha (Frontiers in Global Women's Health, 2023)
Introduction: Improving maternal health and survival remains a public health priority for Sudan.Significant investments were made to expand access to maternal health services, such as through the training and deployment of providers with varying skills and competencies to work across the country.This study investigates trends in the coverage of different birth attendants and their relationship with the maternal mortality ratio (MMR).Methods: Trend analyses were conducted using data from the 2006, 2010, and 2014 Sudan Household surveys. Three categories of birth attendants were identified: 1) skilled birth attendants (SBAs) such as doctors, nurse-midwives, and health visitors, 2) locally certified midwives, and 3) traditional birth attendants (TBAs). Multivariable logistic regression models were used to examine trends in SBAs (vs locally certified midwives and TBAs), locally certified midwives (vs SBA and TBA), and SBA and locally certified midwives by place of birth (health facility and home). The analyses were adjusted for